2010
DOI: 10.1111/j.1751-9004.2010.00291.x
|View full text |Cite
|
Sign up to set email alerts
|

If I Only Had a Membrane: A Review of Amoebic Self Theory

Abstract: Beginning from the premise that organisms must ‘eat, retreat, and excrete’ to survive, Amoebic Self Theory (AST) posits that humans also struggle for survival of the psychological sense of self – engulfing that which is desirable, resisting external threats, and disposing that which is toxic or redundant. These motives manifest across three related but distinct domains – the bodily, the social, and the spatial‐symbolic – as facilitated by a boundary that differentiates ‘self’ from ‘not‐self’. AST‐inspired rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…The results underscore the importance of treating threat not as a single scientific construct but instead as a category of psychologically distinct constructs, each with potentially unique implications. This perspective fits with that of Amoebic Self Theory (Burris & Rempel, 2010) and has also proven productive in research on the psychology of prejudice: different threats predict psychologically distinct forms of prejudice (Cottrell & Neuberg, 2005;Neuberg et al, 2011). More generally, different forms of threat may produce psychologically distinct effects on many phenomena pertaining to social cognition and social behavior.…”
Section: Implications and Future Directionssupporting
confidence: 66%
“…The results underscore the importance of treating threat not as a single scientific construct but instead as a category of psychologically distinct constructs, each with potentially unique implications. This perspective fits with that of Amoebic Self Theory (Burris & Rempel, 2010) and has also proven productive in research on the psychology of prejudice: different threats predict psychologically distinct forms of prejudice (Cottrell & Neuberg, 2005;Neuberg et al, 2011). More generally, different forms of threat may produce psychologically distinct effects on many phenomena pertaining to social cognition and social behavior.…”
Section: Implications and Future Directionssupporting
confidence: 66%
“…While not dismissing the substantial body of research supporting this perspective, we suggested that self-expansion motivation does not necessitate taking others' well-being into account-and therefore can be predominantly self-focused, releasing a cascade of potential negative implications for others. Framed in the context of AST (e.g., Burris & Rempel, 2010), we proposed that such a self-serving engulfment motive could manifest across three conceptually distinct domains of the self: the bodily, the social (interpersonal), and the (spatial)-symbolic. We developed an individual difference measure of the strength of self-serving engulfment motivation across each domain.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that this darker alternative to bilateral inclusion, or social engulfment, is typified by unilateral, self-serving inclusion wherein the self is motivated to benefit from the other (whether intimate partner or stranger) while barring reciprocal access. Burris and Rempel (2010) suggested that "the human capacity to impart meaning to objects and experiences and appropriate them as symbols also enables expansion of the sense of self beyond the body" (pp. 758-759).…”
Section: Social Engulfmentmentioning
confidence: 99%
“…People often describe their self‐concept metaphorically as a physical entity with a core‐like center and an external shell (e.g., “This is who I am on the inside , beneath the surface ”; Landau et al, ). The deeper a concept (e.g., belief) or external entity (e.g., romantic partner) is brought into this core, the more it is considered a part of one's “true self” (Burris & Rempel, , ; Landau et al, ). Because pictorial measures capitalize on this metaphorical description of the self, they are thought to better capture the fusion experience.…”
Section: Measuring Fusionmentioning
confidence: 99%
“…People often become fused with physical objects that are aptly called “possessions” (e.g., clothing, jewelry, and family heirlooms). These objects may have been created through our labor, or we may have acquired them (Belk, ; Burris & Rempel, ; Csikszentmihályi & Rochberg‐Halton, ; Locke, /2009; Prelinger, ). At times, these possessions are used to communicate valued aspects of the self to others (i.e., symbolic self‐completion, Gollwitzer, Wicklund, & Hilton, ).…”
Section: What Can Become Fused With the Self‐concept?mentioning
confidence: 99%